Diffuse pulmonary meningotheliomatosis – a case report - Maasdorp, S D (Afr J Thorac Crit Care Med, 2020)
Diffuse pulmonary meningotheliomatosis is a rare condition of the lung that presents with nonspecific respiratory symptoms, and usually follows a benign course. It should, however, be considered in the differential diagnosis of a miliary pattern on chest-imaging studies, as illustrated in the case reported